Healthy Dietary Habits Score as an Indicator of Diet Quality in New Zealand Adolescents. Issue 6 (17th April 2014) - Wong, Jyh Eiin; Skidmore, Paula M. L.; Williams, Sheila M.; Parnell, Winsome R.
Abstract: Adoption of optimal dietary habits during adolescence is associated with better health outcomes later in life. However, the associations between a pattern of healthy dietary habits encapsulated in an index and sociodemographic and nutrient intake have not been examined among adolescents. This study aimed to develop a behavior-based diet index and examine its validity in relation to sociodemographic factors, nutrient intakes, and biomarkers in a representative sample of New Zealand (NZ) adolescents aged 15–18 y ( n = 694). A 17-item Healthy Dietary Habits Score for Adolescents (HDHS-A) was developed based on dietary habits information from the 2008/2009 NZ Adult Nutrition Survey. Post hoc trend analyses were used to identify the associations between HDHS-A score and nutrient intakes estimated by single 24-h diet recalls and selected nutritional biomarkers. Being female, not of Maori or Pacific ethnicity, and living in the least-deprived socioeconomic quintile were associated with a higher HDHS-A score (all P < 0.001). HDHS-A tertile was associated positively with intake of protein, dietary fiber, polyunsaturated fatty acid, and lactose and negatively with sucrose. Associations in the expected directions were also found with most micronutrients ( P < 0.05), urinary sodium ( P < 0.001), whole blood ( P < 0.05), serum ( P < 0.01), and RBC folate ( P < 0.05) concentrations. This suggests that the HDHS-A is a valid indicator of diet quality among NZ adolescents.